Axial performance of RC columns strengthened with different jacketing methods. (1st March 2020) - Hwang, Yong-Ha; Yang, Keun-Hyeok; Mun, Ju-Hyun; Kwon, Seung-Jun
Highlights: This study proposed a new arrangement for transverse reinforcement in RC jacketing. We provide valuable data on large-scale RC jacket columns under axial loads. We ascertained that the stress–strain curves of concrete confined by jacket section. We demonstrated that reliable confinement be considered in jacket section. Abstract: This study aims to examine the potential of approaches proposed for transverse reinforcement arrangement in the jacket section of existing non-seismic or deficient columns to enhance the axial performance of these columns. To satisfy the requirements for the seismic details of column design specified in ACI 318-14, an original technique of arranging V-clips across the overlapped legs of channel-shape bars was proposed to form peripheral closed-hoops in the jacket section while avoiding the interruption of the existing column. Ten column specimens with large-scale dimensions were prepared by considering the jacketing method and the amount of transverse reinforcement in the jacket section as test parameters, following which they were tested under concentric axial loads by using a 40000-kN-capacity steel frame. In the test, concrete jacket columns prepared using the proposed V-clip technique showed an axial performance equivalent to that of the counterpart concrete jacket columns prepared using prefabricated bar units, the effectiveness of which was previously demonstrated in terms of the enhancement of axial stiffness, strength, and ductility as well as easier buildability for forming peripheral closed-hoops and supplementary ties in the jacket section. The restriction of the opening of the channel-shape bars by V-clips delayed the buckling of longitudinal reinforcing bars and resulted in less severe damage to the core concrete in the jacket section. Thus, concrete jacket columns reinforced with the proposed techniques exhibited higher values of axial ductility than conventional concrete jacket columns or columns jacketed with steel plates and carbon-fiber laminates.